Non-Coding RNAs: Emerging Therapeutic Targets in Spinal Cord Ischemia–Reperfusion Injury - Ling, Xiao; Lu, Jun; Yang, Jun; Qin, Hanjun; Zhao, Xingqi; Zhou, Pengyu; Zheng, Shaoyi; Zhu, Peng (Frontiers in Neurology, 2021)
Pralysis or paraplegia caused by transient or permanent spinal cord ischemia-reperfusion injury (SCIRI) remains as one of the most devastating postoperative complications after thoracoabdominal aortic aneurysm repair, regardless of the improvement of surgical techniques and perioperative strategies. Uncovering the cellular and molecular pathophysiological processes in SCIRI has become a top priority. Recently, the expression, function, and mechanism of ncRNAs in various diseases has drawn wide attention. Non-coding RNAs (ncRNAs) contain a variety of biological functions, but do not code for proteins. Previous studies have shown that ncRNAs play critical roles in cerebral ischemic diseases and SCIRI. The regulatory function of ncRNAs in cerebral ischemic diseases may provide some inspirations for the research of SCIRI. In contrast to cerebral ischemic diseases, the character of ncRNAs in attenuating SCIRI has not been systematically summarized. This review article will be the first time to assemble the knowledge of ncRNAs regulating apoptosis, inflammation, autophagy, oxidative stress to attenuate SCIRI. A better understanding of the functional significance of ncRNAs following SCIRI could help us to identify novel therapeutic targets and develop potential therapeutic strategies. In this review, we will focus on recent researches about the function of nRNAs in SCIRI.